2012
DOI: 10.1002/app.38377
|View full text |Cite
|
Sign up to set email alerts
|

Influence of monosodium glutamate additive on the morphology and permeability characteristics of polyamide dialysis membranes

Abstract: Membranes were prepared with dope solutions of various concentrations of polyamide and monosodium glutamate (MSG) additive for dialysis applications. The results show that the membranes with higher MSG concentrations had higher water uptakes and porosities. The membranes were characterized with scanning electron microscopy (SEM) and atomic force microscopy techniques and evaluated in terms of the permeability of solutes, such as urea and creatinine. The cross-sectional structure of the membranes prepared witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Polyamide membranes are widely used in solid or fluid separation technologies. Numerous studies have demonstrated the competitiveness of polyamide membranes in nanofiltration (NF) [ 1 , 2 ], forward and reverse osmosis [ 2 , 3 , 4 ], dialysis [ 5 ], pervaporation [ 6 , 7 , 8 , 9 , 10 ], and gas separation [ 11 , 12 , 13 ]. NF is the most common membrane technology for water or liquid separation, and it is usually applied to industries such as water [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], food [ 21 , 22 , 23 , 24 ], textile [ 25 , 26 , 27 ], mining [ 28 , 29 , 30 , 31 ], agricultural [ 32 , 33 , 34 ], pharmaceutical, and biotechnological industries [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide membranes are widely used in solid or fluid separation technologies. Numerous studies have demonstrated the competitiveness of polyamide membranes in nanofiltration (NF) [ 1 , 2 ], forward and reverse osmosis [ 2 , 3 , 4 ], dialysis [ 5 ], pervaporation [ 6 , 7 , 8 , 9 , 10 ], and gas separation [ 11 , 12 , 13 ]. NF is the most common membrane technology for water or liquid separation, and it is usually applied to industries such as water [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ], food [ 21 , 22 , 23 , 24 ], textile [ 25 , 26 , 27 ], mining [ 28 , 29 , 30 , 31 ], agricultural [ 32 , 33 , 34 ], pharmaceutical, and biotechnological industries [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these polymeric thin films, nylon is the most desirable material and is proven to be a suitable immobilization platform . This polymer comprises of high mechanical strength, good stability, and high resistance toward microbial attack . For example, Nan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Among these polymeric thin films, nylon is the most desirable material and is proven to be a suitable immobilization platform. 29 This polymer comprises of high mechanical strength, [30][31][32] good stability, and high resistance toward microbial attack. 33 For example, Nan et al 34 and Scampicchio et al 35 exploited the uses of nylon film as an enzyme-immobilized platform to detect glucose in human serum.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations